Solid state quantum chemistry of solids : the chemical bond and energy bands in tetrahedral semiconductors - Levin, Alexander A. (New York : McGraw Hill Education, 1976)
This book is addressed to chemists and physicists, both experts and students, interested in the theory of the chemical bond and primarily to those persons involved with problems dealing with the electron structure of solids.
Chapter 1. One-electron approximation in the theory of the chemical bond -- Chapter 2. Band theory of solids -- Chapter 3. Chemical bond and structure of energy -- Chapter 4. Chemical bond and band structure of covalent crystals, conduction band and complete band structure.
Includes bibliographical references and index.
Keywords: THEORY -- CHEMICAL BOND -- SEMICONDUCTOR